Student Grade Association Analysis with Apriori Algorithm - Khoiruzzidan, Ilma; Iswari, Lizda (Department of Informatics Universitas Islam Indonesia, 2024)
This study focuses on applying the Apriori algorithm to course grades of 150 students. The research aims to uncover correlations between course grades, providing insights for both the researcher and the institution. Data was directly extracted from the student academic database. The Apriori algorithm was implemented in three scenarios with varying minimum support and confidence thresholds. The final results depict patterns in course grades that tend to co-occur. Among the three scenarios, the combination of Game Development with an A grade, Informatics Fundamentals with an A grade, and Advanced Math with an A grade yielded the highest values, with a support of 26% and confidence of 88.6%.